Biographies and Memoirs of Arab and Foreign Women: A Comparative Study - Al-Tamimi, Amal Bint Muhammad (Arts for Linguistic & Literary Studies, 2021)
This research aims to compare the biographies of Arab and foreign women and their memoirs. The selected books of the study sample were divided into three sections, namely: Arabic texts, translated texts by Arab women writers who wrote their biographies in foreign languages, and foreign texts by foreign writers. We attached a contrast table of the most important common issues between Arab and foreign women's biographies, such as (medical history - prison experience - professional history, etc.). We monitored the unique experiences of Arab women and did not find similar experiences in foreign texts, such as divorce and scholarship cases. The study concluded with the most important findings, including the following: It turned out that the woman wrote about her life in many different ways; some of them wrote in the form of notes and others in the form of fictional storytelling. Moreover, it became clear that the experience of the Arab woman is similar to that of a foreigner in general issues such as social and political activities, and differs in special topics such as the issue of the homeland and colonialism, marriage and divorce, as well as the result related to gender language consciousness of women in their biographies. The recipient – including critics, publishing houses, and bookstores – is responsible for creating such a complexity.